Segmentation of the art and culture labor market in Argentina 2016-2019 - Marina Tortul; Viviana Leonardi (Población y Desarrollo, 2023)
The art and culture sector has been historically linked to leisure and individual vocation, dissociating artistic labor from its economic remuneration and social benefits. The hypothesis of this paper is that these characteristics lead to a duality of the labor market in the sector. That is, a segmented labor market, where two types of workers coexist. Some linked to the formal sector that enjoy stability and social security. Others, linked to the informal sector, who lack these benefits. The objective of the research is to recognize differential characteristics between formal and informal workers in the Argentine art and culture sector in the period 2016-2017. For this, a descriptive and exploratory methodology is implemented based on data provided by the Encuesta Permanenrte de Hogares (INDEC 2016, 2017, 2018 and 2019). The main results corroborate the paper hypothesis. Thus, the presence of a segmented labor market is verified where workers in the formal sector enjoy more favorable working conditions and higher labor income than those in the informal sector. It is considered that this work contributes to the understanding of the current situation of the labor market of art and culture in Argentina, at the same time that it outlines some policy actions to face the informality of the same.